Response of noctilucent cloud brightness to daily solar variations. (April 2018) - Dalin, P.; Pertsev, N.; Perminov, V.; Dubietis, A.; Zadorozhny, A.; Zalcik, M.; McEachran, I.; McEwan, T.; Černis, K.; Grønne, J.; Taustrup, T.; Hansen, O.; et al.
Abstract: For the first time, long-term data sets of ground-based observations of noctilucent clouds (NLC) around the globe have been analyzed in order to investigate a response of NLC to solar UV irradiance variability on a day-to-day scale. NLC brightness has been considered versus variations of solar Lyman-alpha flux. We have found that day-to-day solar variability, whose effect is generally masked in the natural NLC variability, has a statistically significant effect when considering large statistics for more than ten years. Average increase in day-to-day solar Lyman-α flux results in average decrease in day-to-day NLC brightness that can be explained by robust physical mechanisms taking place in the summer mesosphere. Average time lags between variations of Lyman-α flux and NLC brightness are short (0–3 days), suggesting a dominant role of direct solar heating and of the dynamical mechanism compared to photodissociation of water vapor by solar Lyman-α flux. All found regularities are consistent between various ground-based NLC data sets collected at different locations around the globe and for various time intervals. Signatures of a 27-day periodicity seem to be present in the NLC brightness for individual summertime intervals; however, this oscillation cannot be unambiguously retrieved due to inevitable periods of tropospheric cloudiness. Highlights: Analyzed long-term data sets of ground-based NLC observations around the globe. Observational evidence for NLC brightness response to day-to-day solar variability. Average increase in solar UV changes leads to average decrease in NLC brightness. Average time lags are short and vary between 0 and 3 days.